Addition of Catfish (Pangasius hypophthalmus) Bone Meal as a Source of Calcium in Catfish Nugget - Azlaini Yus Nasution (LPPM Universitas Abdurrab, 2022)
Fish bones contain calcium which can be used as a source of calcium that the body needs. Calcium functions as the formation and maintenance of bones and teeth. The purpose of this study was to determine calcium levels in catfish nuggets after the addition of bone meal derived from catfish. The formula made consisted of F1 (nuggets without the addition of bone meal or calcium carbonate), F2 (nuggets with the addition of catfish bone meal), and F3 (nuggets with the addition of calcium carbonate). Analysis of calcium content using atomic absorption spectrophotometry method. The calcium content in catfish nuggets were F1=350.010 mg/100 grams, F2=1025.335 mg/100 grams, and F3=1498,058 mg/100 grams. Bone flour from catfish added can increase the calcium content in catfish nuggets.